2003
DOI: 10.1074/jbc.m210077200
|View full text |Cite
|
Sign up to set email alerts
|

The a-Subunit of the V-type H+-ATPase Interacts with Phosphofructokinase-1 in Humans

Abstract: V-type or H؉ -ATPases are a family of ATP-dependent proton pumps that move protons across the plasma membrane at specialized sites such as kidney epithelial cells and osteoclasts as well as acidifying intracellular compartments. The 100-kDa polytopic a-subunit of this group of ATPases is suggested to play an important role in coupling the two functions of the pump, ATP hydrolysis and proton transport. In man, different a-subunit isoforms are encoded by four genes. ATP6V0A4 encodes a4, which is expressed apical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 48 publications
5
83
0
Order By: Relevance
“…4a), indicating a cytoplasmic orientation. A cytoplasmic orientation of the C-terminal tail is also in agreement with previous studies showing that the C terminus of subunit a is able to bind the glycolytic enzyme phosphofructokinase, as demonstrated by co-immunoprecipitation (24), and that a GFP tag attached at the C terminus of subunit a from Dictyostelium can be proteolytically removed in intact endosomes (25). The former result does not rule out an extracellular orientation for the C terminus of subunit a as a number of cytoplasmic proteins (such as HSP90) have been shown to be released into the extracellular medium (45).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…4a), indicating a cytoplasmic orientation. A cytoplasmic orientation of the C-terminal tail is also in agreement with previous studies showing that the C terminus of subunit a is able to bind the glycolytic enzyme phosphofructokinase, as demonstrated by co-immunoprecipitation (24), and that a GFP tag attached at the C terminus of subunit a from Dictyostelium can be proteolytically removed in intact endosomes (25). The former result does not rule out an extracellular orientation for the C terminus of subunit a as a number of cytoplasmic proteins (such as HSP90) have been shown to be released into the extracellular medium (45).…”
Section: Discussionsupporting
confidence: 78%
“…Previous data from our laboratory analyzing the membrane topology of subunit a led to a model of the protein in which the cytoplasmic N-terminal domain was followed by a C-terminal domain containing nine transmembrane helices, placing the C terminus on the lumenal side of the membrane (15). Other data, however, have suggested that the C terminus is located on the cytoplasmic rather than the lumenal side of the membrane (24,25). To further address the membrane topology of subunit a, we have employed a combination of cysteine-scanning mutagenesis and chemical modification with membrane permeant and impermeant reagents.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Crosslinking, two-hybrid screening, coimmunoprecipitation, and electron microscopy showed that the a-subunit isoforms directly interact with A-, E-, H-, C-, and G-subunits of the V 1 sector [9][10][11][12][13] as well as with c-and d-subunits of the V o sector. 2,[14][15][16] Recently, it has also been shown that the V-ATPase a-subunit directly assembles with proteins that are not part of the V-ATPase complex including: (i) aldolase B, 17,18 (ii) phosphofrucktokinase-1, 19,20 (iii) calmodulin, 21 and (iv) t-SNARES syntaxin and SNAP-25. 22 However, the mechanisms and molecular details of interactions with these proteins remain poorly understood, mainly due to the lack of a high-resolution structure of the a-subunit and the absence of studies designed for mapping interaction sites on both the a-subunit and its associated proteins.…”
Section: Introductionmentioning
confidence: 99%
“…During the logarithmic phase of growth, high glucose levels of the medium lead to the synthesis of high amounts of ATP by the glycolytic pathway. Several studies have demonstrated a direct interaction between glycolytic enzymes, such as aldolase (43)(44)(45) or phosphofructokinase-1 (46), and several subunits of the V-ATPase. Moreover, it has been postulated that the V-ATPase and glycolytic enzymes form a complex in the vacuolar membrane to maximize the efficiency of energy provision to acidify the vacuole.…”
Section: Down-regulation Of V-atpase Activity Maintains a Normal Hmentioning
confidence: 99%